Circadian rhythms, refractive development, and myopia - Chakraborty, Ranjay (Ophthalmic Physiol Opt, 2018)
PURPOSE: Despite extensive research, mechanisms regulating postnatal eye growth and those responsible for ametropias are poorly understood. With the marked recent increases in myopia prevalence, robust and biologically-based clinical therapies to normalize refractive development in childhood are needed. Here, we review classic and contemporary literature about how circadian biology might provide clues to develop a framework to improve the understanding of myopia etiology, and possibly lead to rational approaches to ameliorate refractive errors developing in children. RECENT FINDINGS: Increasing evidence implicates diurnal and circadian rhythms in eye growth and refractive error development. In both humans and animals, ocular length and other anatomical and physiological features of the eye undergo diurnal oscillations. Systemically, such rhythms are primarily generated by the ‘master clock’ in the surpachiasmatic nucleus, which receives input from the intrinsically photosensitive retinal ganglion cells (ipRGCs) through the activation of the photopigment melanopsin. The retina also has an endogenous circadian clock. In laboratory animals developing experimental myopia, oscillations of ocular parameters are perturbed. Retinal signaling is now believed to influence refractive development; dopamine, an important neurotransmitter found in the retina, not only entrains intrinsic retinal rhythms to the light:dark cycle, but it also modulates refractive development. Circadian clocks comprise a transcription/translation feedback control mechanism utilizing so-called clock genes that have now been associated with experimental ametropias. Contemporary clinical research is also reviving ideas first proposed in the nineteenth century that light exposures might impact refraction in children. As a result, properties of ambient lighting are being investigated in refractive development. In other areas of medical science, circadian dysregulation is now thought to impact many non-ocular disorders, likely because the patterns of modern artificial lighting exert adverse physiological effects on circadian pacemakers. How, or if, such modern light exposures and circadian dysregulation contribute to refractive development is not known. SUMMARY: The premise of this review is that circadian biology could be a productive area worthy of increased investigation, which might lead to the improved understanding of refractive development and improved therapeutic interventions.